"Auricular reconstruction: A sociocultural, surgical and scientific perspective". Issue 8 (August 2020) - Jovic, Thomas H.; Stewart, Ken; Kon, Moshe; Whitaker, Iain S.
Summary: The functional and sociocultural role of the auricle has been prevalent in art, literature and history for millennia. It is no surprise, therefore, that auricular anomalies can be associated with affective disorders and impaired academic performance in children. The challenge of auricular reconstruction has captured the attention of surgical innovators for millennia with the earliest records of auricular reconstruction documented in the Edwin Smith Surgical Papyrus dating back to 3000 BCE. Since the 19th century, however, the interest in the ambition partial and total auricular reconstruction witnessed a rebirth, with refinements in frame construction, projection and skin coverage improving exponentially over the last two centuries. The gold standard auricular reconstruction practices today have their roots in these historical milestones, and form a solid foundation for the introduction of technological advancements such as 3D bioprinting and composite tissue allotransplantation into future auricular reconstruction practice. The aim of this review is to outline the sociocultural role of the auricle, the history and evolution of auricular reconstruction surgery and to provide an insight into potential future avenues of restoring auricular form and function.